2021
DOI: 10.3390/curroncol28060378
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in the First-Line Setting in Wild-Type NSCLC

Abstract: Treatment algorithms in the treatment of advanced non-small cell lung cancer (NSCLC) continue to evolve as new therapeutics show positive efficacy improvements. This review article summarizes the data for the use of immunotherapy for treatment in first-line stage IV NSCLC, organized by the following four sections: single-agent immunotherapy, immunotherapy and chemotherapy, dual immunotherapy, and dual immunotherapy and chemotherapy. The results are summarized and tabulated. Finally, application of the trial da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In the context of NSCLC, PD-1 and PD-L1 inhibitors such as pembrolizumab, nivolumab, and atezolizumab in combination with chemotherapy have become the standard-of-care in frontline therapy after demonstrating significant improvements over chemotherapy with regards to ORR, PFS, and OS in patients without EGFR-activating mutations ( 180 ). However, much lower efficacy has been noted if EGFR-driver mutations are present ( 181 ).…”
Section: Engaging Adaptive Immunity In Targeting Egfr-expressing Tumorsmentioning
confidence: 99%
“…In the context of NSCLC, PD-1 and PD-L1 inhibitors such as pembrolizumab, nivolumab, and atezolizumab in combination with chemotherapy have become the standard-of-care in frontline therapy after demonstrating significant improvements over chemotherapy with regards to ORR, PFS, and OS in patients without EGFR-activating mutations ( 180 ). However, much lower efficacy has been noted if EGFR-driver mutations are present ( 181 ).…”
Section: Engaging Adaptive Immunity In Targeting Egfr-expressing Tumorsmentioning
confidence: 99%
“…Immunotherapy combined with chemotherapy can be considered for first-line therapy if PD-L1 expression is found on less than 50% of tumor cells. For advanced NSCLC patients with PD-L1 expression on less than 1% of TC or regardless of this expression, pembrolizumab or nivolumab or atezolizumab could be used in second-line therapy in patients who have not previously received immunotherapy (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoint inhibitor (ICI) stimulates the immune system to release potent T cells, so as to eliminate cancer cells ( 11 ). Although studies have shown that ICI does not exert significant efficacy in NSCLC with driver mutations ( 12 , 13 ), however, new evidence suggests the emergence of ICI has dramatically altered the management and prognosis of wild-type mNSCLC and enable greater possibility of long-term survival ( 3 6 , 14 17 ).…”
Section: Introductionmentioning
confidence: 99%